New visions in performance : the impact of digital technologies - Carver, Gavin; Beardon, Colin, 1945- (Innovations in art and design., 2004)
"This book features the work of twelve performers and academics who are involved in the integration of digital technologies into theatrical performance. The chapters are all analytical case studies (some written by the artists themselves) of creative practices which include insights into the very latest developments in the confluence of performance and technology."--Jacket